PDPGR (PROGRAM DAERAH PEMBERDAYAAN GOTONG GOYONG) SEBAGAI INOVASI DALAM PENANGANAN PERCEPATAN REHABILITASI DAN REKONSTRUKSI PASCA GEMPA BUMI DI KABUPATEN SUMBAWA BARAT - Saleh, Muhammad; Harjito (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
This study aims to determine the role and success indicators of PDPGRas an innovation in handling accelerated rehabilitation and reconstruction after the earthquakein West Sumbawa district. This research uses a qualitative approach. Techniquedata collection using observation, interviews, and documentationWest Sumbawa district government regulations and policies related to PDPGR.Informants were selected by purposive sampling. The selected informants were 7 peoplewhich is a steering team at the district level, PDPGR agents, traditional leaders, leadersreligion, and community leaders. The data obtained were analyzed using three pathsnamely reduction, presentation of data, and drawing conclusions made at the timedata collection in progress. The validity of the data was tested using triangulation techniquessource. The results showed that the role of PDPGR as a treatmentacceleration of post-earthquake rehabilitation and reconstruction, among others; 1) Make it easy andaccelerating the formation of community groups which are the basic rules in the processpost-disaster rehabilitation and reconstruction. 2) Assisting the community data collection processaffected by the earthquake quickly and completely. This is due to the PDPGR agentstructured and massive up to the block level incorporated in Pokmas Plus. 3)Help speed up the administrative process such as making RAB, disbursing funds,management to the BPBD, and making LPJ. This is because PDPGR agents haveexperience with the home rehabilitation program over the past 2 years. 4)Provide space for the community to actively participate in acceleratingthe rehabilitation and reconstruction process. PDPGR success indicator in acceleratingThe rehabilitation and reconstruction process includes a shorter processing timerather than the time given by BNPB and the quantity of work completed.From the data, it was found that more than 95% of the people's houses were affected by the earthquakeresolved quickly both for the category of Light Damage (RR), Moderately Damaged (RS),and Heavy Damage (RB).